(untitled) (Research, Society and Development, 2024)
Oral rehabilitation through dental implants has become one of the main means for restoring function and aesthetics to patients who have partially or totally lost their teeth. Since then, new implant systems have emerged, including the cone-morse system. Thus, this study aims to review the literature in order to analyze the clinical application and benefits of using the cone-morse implant. This literature review was performed from the selection of scientific articles with online publication. The review was conducted in the main national and international databases, namely: SCIELO, Biomedical Journal Literature at the service of the National Library of Medicine (MEDLINE/PubMed) and CAPES Portal. The results of the studies showed that the cone-morse system has advantages over other systems, since it presents more stability, less contamination by bacteria and better proservation of periodontal and bone structures. Thus, it was concluded that the cone-morse system presents a good prognosis of maintenance and functioning in oral rehabilitation, being a treatment option with good applicability in dentistry.